Process‐wide control and automation of an integrated continuous manufacturing platform for antibodies. Issue 5 (17th February 2020) - Feidl, Fabian; Vogg, Sebastian; Wolf, Moritz; Podobnik, Matevz; Ruggeri, Caterina; Ulmer, Nicole; Wälchli, Ruben; Souquet, Jonathan; Broly, Hervé; Butté, Alessandro; Morbidelli, Massimo
Abstract: Integrated continuous manufacturing is entering the biopharmaceutical industry. The main drivers range from improved economics, manufacturing flexibility, and more consistent product quality. However, studies on fully integrated production platforms have been limited due to the higher degree of system complexity, limited process information, disturbance, and drift sensitivity, as well as difficulties in digital process integration. In this study, we present an automated end‐to‐end integrated process consisting of a perfusion bioreactor, CaptureSMB, virus inactivation (VI), and two polishing steps to produce an antibody from an instable cell line. A supervisory control and data acquisition (SCADA) system was developed, which digitally integrates unit operations and analyzers, collects and centrally stores all process data, and allows process‐wide monitoring and control. The integrated system consisting of bioreactor and capture step was operated initially for 4 days, after which the full end‐to‐end integrated run with no interruption lasted for 10 days. In response to decreasing cell‐specific productivity, the supervisory control adjusted the loading duration of the capture step to obtain high capacity utilization without yield loss and constant antibody quantity for subsequent operations. Moreover, the SCADA system coordinated VI neutralization and discharge to enable constant loading conditions on the polishing unit. Lastly, the polishing was sufficiently robust to cope with significantly increased aggregate levels induced on purpose during virus inactivation. It is demonstrated that despite significant process disturbances and drifts, a robust process design and the supervisory control enabled constant (optimum) process performance and consistent product quality. Abstract : The automation of an end‐to‐end integrated process for the production of an antibody from an instable cell line is presented. Based on robust process development and a supervisory control and data acquisition system, process drifts and disturbances could be rejected. Thereby, constant process performance and consistent product quality was obtained throughout the entire run.